In-line inspection of pipeline crack based on biased AC field measurement - Shuangcheng FU FU; Bingfeng YU; Jiaxing XIN; Rong DING; Fan YANG; Hongwei LYU; Jinzhong CHEN; Xiaokang WAN (You-qi chuyun)
Objective The traditional magnetic flux leakage (MFL) testing technique for pipelines has been found to be insufficient in detecting crack defects with a small angle to the magnetic field lines. As a result, an inspection method that can accurately detect such defects is urgently needed to ensure the safe operation of oil and gas pipelines. Methods This paper introduces an in-line inspection method for pipeline cracks based on a biased AC field measurement (B-ACFM) technique, which combines the strengths of both MFL testing and ACFM. The initial study focused on examining the variations in internal magnetic field and surface eddy current field distributions of specimens based on crack angles, in alignment with the fundamental principle of B-ACFM. Subsequently, a finite element analysis model was developed to elucidate the impacts on internal magnetic field and surface eddy current field distributions in the presence or absence of cracks. Furthermore, an experimental platform was constructed to validate the viability of the proposed method utilizing B-ACFM. Results For cracks positioned at varying angles from 0° to 15° on the inner wall, the signal characteristics displayed a wave trough followed by a wave peak. Conversely, for angles spanning from 15° to 90°, a phase reversal occurred, manifesting as a wave peak followed by a wave trough in the signal features. Regarding inner wall cracks ranging from 0° to 45°, the peak-to-valley value (Umax-min) of crack response signals exhibited a gradual decrease as the angle increased. However, beyond 45°, Umax-min rose with increasing angle. In terms of cracks with differing depths within the inner and outer walls, the response signals presented wave peaks followed by wave troughs, and Umax-min steadily ascended with increasing crack depth in both the inner and outer walls. Conclusion The suggested method showcases its efficacy in accurately detecting 0.3 mm wide cracks at various angles and 0.5 mm wide cracks angled at 90°, with differing depths in the inner pipeline wall. The established minimum detection depth is confirmed to reach 30% of the wall thickness for 0.5 mm wide cracks at a 90° angle in the outer pipeline wall. Furthermore, this method exhibits quantitative detection proficiency for cracks positioned at different angles on the inner pipeline wall and for those exhibiting varying depths within both the inner and outer pipeline walls.